Correlation between continuous assessment and students’ performance in Islamic studies - Jamiu Abdur-Rafiu; U Ajidagba; Masood Rafiu (Intelektual Pustaka Media Utama, 2020)
This study investigated the correlation between continuous assessment scores and Islamic Studies students’ performance in WASSCE and NECO Examinations in Ilorin, Nigeria. The instruments used were the copy of cumulative continuous assessment scores for three consecutive years (2011-2013) in Islamic Studies; (ii) the 2011-2013 Islamic Studies may/June SSCE computerized result sheets sent to each school by WAEC and NECO. The results of students were analysed using Pearson Product Moment Correlation Coefficient (r) and regression. The findings showed that: (i) Students’ performance in Islamic Studies in NECO and WASSCE of the years under study (2011-2013) is fluctuating. (ii). Significant relationship exists between students’ continuous assessment scores and their performance in Islamic Studies in SSCE conducted by NECO. (iii). There is a significant relationship between students’ continuous assessment scores and their performance in Islamic Studies in WASSCE. (iv). There is a significant correlation among the school type of Students, their continuous assessment scores and their performance in Islamic Studies. Based on the findings of the study, it was recommended among others that there is a need to encourage Islamic Studies teachers in both public and private senior secondary schools to attach importance to the proper and regular conduct of continuous assessments.